Linguistic Ellipsis in English: Analyzing Types and Functions of Elliptic Sentences (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes linguistic ellipsis and elliptic sentences in English language, their types and study fields in order to produce a sentence fragment or an unfinished phrase, the ellipsis remnant of a syntactic omission is purposefully left grammatically defective or incomplete. This occurrence is known as ellipsis.